2020
DOI: 10.1039/c9sc05050g
|View full text |Cite
|
Sign up to set email alerts
|

Sodium caseinate as a particulate emulsifier for making indefinitely recycled pH-responsive emulsions

Abstract: An unprecedented pH-responsive emulsion is shaped by utilizing pure sodium caseinate (NaCas) as the sole emulsifier for recyclable interfacial catalysis. This emulsion could be reversibly switched on and off over 100 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 40 publications
(42 reference statements)
0
35
0
Order By: Relevance
“…However, Xi et al demonstrated that an emulsion prepared with sodium caseinate (forming micelles) as the sole emulsifier could be recycled over 100 times as its pHresponsive property was maintained even in a saturated salt solution (NaCl B6.1 M). 115 Thermo-responsive systems on the other hand are energy demanding and if used in the field of biocatalysis, the enzyme has to be stable at the temperature where the stabilization/destabilization occurs. 98 Described below are examples of various methods used to recover the catalyst other than centrifugation.…”
Section: Recyclability and Re-usability Of Catalystsmentioning
confidence: 99%
“…However, Xi et al demonstrated that an emulsion prepared with sodium caseinate (forming micelles) as the sole emulsifier could be recycled over 100 times as its pHresponsive property was maintained even in a saturated salt solution (NaCl B6.1 M). 115 Thermo-responsive systems on the other hand are energy demanding and if used in the field of biocatalysis, the enzyme has to be stable at the temperature where the stabilization/destabilization occurs. 98 Described below are examples of various methods used to recover the catalyst other than centrifugation.…”
Section: Recyclability and Re-usability Of Catalystsmentioning
confidence: 99%
“…Although at higher protein concentrations (such as those studied here) BSA interfacial tension is further reduced, the low pH sensitivity remains. NaCAS, possesses a disordered structure and although typically associates into spherical micelles of 20-40 nm in diameter under neutral and weakly basic conditions, it can form colloidal particles of dimensions in the order of 200-300 nm at more acidic conditions (pH 5.1) [36] closer to its isoelectric point (~pH 4.2) [37]. Sodium caseinate partial aggregation could explain the higher equilibrium IFT values measured here (at pH 5) compared to those reported for the protein (~3 mN m -1 ) at its native pH (pH ≈ 6.8) [38].…”
Section: Emulsion Interface Droplet Size and Stabilitymentioning
confidence: 99%
“…This would indicate that the globular structure of BSA, although potentially losing at least part of this higher order structure upon adsorption, creates a denser and higher (DMP) release energy barrier than NaCAS. What is more, if the aggregates that both proteins are expected to form at pH 5 persist during emulsification and take part in the interfaces created, then their dissimilar dimensions could potentially give rise to barriers of different thicknesses, with the BSA larger colloidal structures thus expected to more efficiently retard active migration [34], [36].…”
Section: Interfaces Stabilised By Ssl or Proteinsmentioning
confidence: 99%
“…[28][29] In particular, the amphiphilic nature of proteins allows its supported catalyst to anchor on the interface, thereby affecting the catalytic efficiency. 30 This study reported the use of smart protein nanoparticles to anchor artificial enzymes (Au NCs), combined with glucose oxidase (GOx) of the aqueous phase, for realizing PIC cascade reaction. Specifically, an Au/ZCPOP catalyst (ZCPOPs-Au NC) was developed by growing Au NCs in situ onto ZCPOPs.…”
Section: Introductionmentioning
confidence: 99%